Immune-related adverse events of COVID-19 vaccination in skin cancer patients receiving immune-checkpoint inhibitor treatment - Strobel, Sophia; Machiraju, Devayani; Kälber, Katharina; Hassel, Jessica C. (Cancer immunology immunotherapy, 2021)
To date, few data are available regarding Adverse events (AEs) in cancer patients who are vaccinated for coronavirus disease 2019 (COVID-19) while being actively treated with Immune-checkpoint inhibitors (ICIs). We aimed to assess the safety of COVID-19 vaccines approved in Germany. Specifically, we investigated the frequency of general side effects and immune-related AEs of COVID-19 vaccination. A triage survey was used to collect the following information for patients with metastatic skin cancer: vaccine type, date of receipt of each dose of vaccine, and self-reported side effects. Clinical data were retrieved from the patients’ medical records. Of 130 patients with metastatic skin cancer, 89 patients were on immunotherapy and received COVID-19 vaccination. Of these 89 patients (median age: 64 years; 57 [64%] men), 89% had melanoma, and 71% received ICI therapy with a PD-1 antibody. Eighty-eight percent received an mRNA-based COVID-19 vaccination. The median follow-up time was 125 days after the first vaccination, and 84 days after the second. The most common observed side effects were mild to moderate pain at the injection site (40%), followed by fatigue (24%). Grade 3 irAEs were reported in eight patients, seven of whom were on nivolumab plus ipilimumab combination treatment. Of the 19 patients vaccinated within 72 h before/after ICI, five developed irAEs within 17 days (1-17 days). This small cohort study suggests that approved COVID-19 vaccinations are safe for use in cancer patients receiving ICIs. However, some precautions should be taken, especially regarding the timing of vaccination and ICI treatment.
Gesehen am 06.06.2023